Amalan jagaan diri selepas Mastektomi dalam kalangan pengidap kanser payudara di Hospital Universiti Sains Malaysia - Khairul Mardhiyyah, Abd. Halim (PPSP, Universiti Sains Malaysia, 2007)
This study is to explore self-care activity after mastectomy among breast cancer patient in H USM. This study is also to explore about the demography of breast cancer patient who undergone mastectomy, to identify the level of selfcare and its relationship with age and breastfeeding. The location of this study is at Surgery Clinic and Oncology Clinic, HUSM. Self-care itself is measured using an instrument that modified from a questionnaire which was adapted from Van Su (2005). This study is using Orem Theory. The relationship between post mastectomy self-care with age and breastfeeding is identified using chi-square test. According to the result of the study, the level of self-care among breast cancer patient who undergone mastectomy is moderate and there is an association between self-care and age of the patient As the conclusion, in order to enhance the level of self-care among breast cancer patient who undergone mastectomy everybody especially healthcare provider should consider about the patients' demography. This is because there are possibilities that the demographical factor is affected their self care activities.